The Effect of Filteret Sugarcane Juice in Egg Yolk Citrate on Viability and Spermatozoa Abnormality, and pH of Bali Catle Semen - Rindiyani Y Tanii; Agustinus A Dethan; Theresia Ika Purwantiningsih (Program Studi Peternakan, Fakultas Pertanian Universitas Timor, 2022)
This study aims to determine the effect of the sugarcane juice diluent in egg yolk citrate on viability, spermatozoa abnormality, and pH of Bali bull semen. This study has been carried out in Poultry Housing of Animal Science Study Program, and the Laboratory of the Faculty of Agriculture, University of Timor. Semen is collected from a a bull, ± 4.5 years old, in healthy condition. The method used in this study was a completely randomized design method with 5 treatments and 4 replications. The treatment giving are: T0 (diluent citrate-egg yolk without sugarcane juice); T1 (diluent citrate-egg yolk + 5ml sugarcane juice); T2 (diluent citrate-egg yolk + 10 ml sugarcane juice); T3 (diluent citrate-egg yolk + 15 ml sugarcane juice) and T4 (diluent citrate-yolk + sugar cane juice 20 ml). The variables measured were viability, abnormal spermatozoa, and semen pH of Bali bull. The results showed that T4 treatment with a 20 ml sugarcane juice level showed the best value for spermatozoa viability (92.875%), spermatozoa abnormality (6.375%), and semen pH (6.6). Conclusion: that the level of 20 ml of sugarcane juice in semen diluent can maintain the life of Bali bull spermatozoa.